Critical Congenital Heart Disease in Newborn: Early Detection, Diagnosis, and Management - Herick Alvenus Willim; Cristianto; Alice Inda Supit (HM Publisher, 2021)
Critical congenital heart disease (CHD) is a type of CHD that requires early intervention in the first year of life to survive. Morbidity and mortality increases significantly if newborns with critical CHD experience delay in the initial diagnosis and management. The infants may develop cyanosis, systemic hypoperfusion, or respiratory distress as the main manifestations of critical CHD. Pulse oximetry screening for early detection of critical CHD must be performed in newborns after 24 hours of age or before discharge from hospital. Generally, infants with critical CHD require patency of the ductus arteriosus with infusion of prostaglandin to maintain pulmonary or systemic blood flow. After initial management, the infants must be immediately referred to tertiary care center for definitive intervention. Keywords: congenital heart disease, duct-dependent circulation, ductus arteriosus, prostaglandin